Price, Product Quality, and Packaging in Yumsbite Purchase Decisions: Harga, Kualitas Produk, dan Kemasan dalam Keputusan Pembelian Yumsbite - Resti Haryati; Fitria Rahmona; Zul Afdal; Abror (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The Indonesian snack food industry continues to grow, with consumer preferences increasingly shaped by product quality and experience. Specific Background: In micro and small enterprises (MSMEs) like Yumsbite Donuts, purchasing decisions are often influenced by price, packaging, and perceived product value. Knowledge Gap: While many studies analyze these variables quantitatively, there is limited literature mapping that visualizes trends, author networks, and research clusters in this field. Aims: This study aims to systematically analyze the influence of price, product quality, and packaging on purchase decisions through a bibliometric approach using VOSviewer. Results: Analysis of 30 selected articles reveals three main research clusters, with product quality and packaging emerging as dominant themes, while price is comparatively less discussed. Novelty: Unlike previous regression-based studies, this research maps the intellectual structure and thematic evolution of the literature, uncovering underexplored areas such as visual branding and consumer perception. Implications: The findings suggest that MSMEs should prioritize product quality and packaging strategies over pricing tactics to enhance consumer purchase decisions, offering a practical reference for marketing development and a foundation for future research directions.Highlight : Product quality and packaging are the most dominant factors influencing purchase decisions. Price is less emphasized in literature compared to quality and packaging. Bibliometric analysis helps identify research clusters and practical strategies for MSMEs. Keywords : Price, Product Quality, Packaging, Purchase Decisions, Snack MSMEs